2017
DOI: 10.1080/03057925.2017.1369393
|View full text |Cite
|
Sign up to set email alerts
|

Global citizens or global workers? Comparing university programmes for global citizenship education in Japan and the UK

Abstract: In recent years, higher education (HE) institutions have increasingly been articulating the need to produce global citizens capable of meeting the social, political and economic demands of the 21st Century. The implementation of global citizenship programmes at the university level has been taking place against a backdrop of growing internationalization and marketization in higher education, leading some to conclude that universities are cultivating global workers rather than global citizens. This small-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
0
23
0
3
Order By: Relevance
“…In a study investigating how schools fulfil their commitment to GCE (since it has become an agenda in the national curriculum for promoting social justice), it is found that influenced by Korea's Confucian collectivist cultural heritage, the imbalanced rhetoric about the international positions between some Western countries and some non-Western countries caused reproduction of neoliberal hegemonies and inequality (Cho and Mosselson 2018). In Japan, however, another developed Asian country, a case study found that GCE has been adapted in a way that follows neoliberal objectives targeting employability with a strengthened notion of ethnic identity (Hammond and Keating 2018).…”
Section: Global Citizenship Education and The Relevant Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating how schools fulfil their commitment to GCE (since it has become an agenda in the national curriculum for promoting social justice), it is found that influenced by Korea's Confucian collectivist cultural heritage, the imbalanced rhetoric about the international positions between some Western countries and some non-Western countries caused reproduction of neoliberal hegemonies and inequality (Cho and Mosselson 2018). In Japan, however, another developed Asian country, a case study found that GCE has been adapted in a way that follows neoliberal objectives targeting employability with a strengthened notion of ethnic identity (Hammond and Keating 2018).…”
Section: Global Citizenship Education and The Relevant Practicesmentioning
confidence: 99%
“…Moreover, the advocacy-oriented theorisation of GCE is validated in several empirical studies. Findings in some negative cases, including South Korea (Cho and Mosselson 2018), Japan (Hammond and Keating 2018) and Ghana (Howard et al 2018), suggest that to achieve the designed GCE outcomes, social justice and equity cannot be avoided as otherwise, reverse outcomes of reinforced neoliberalism and post-colonialism will be caused.…”
Section: Introductionmentioning
confidence: 99%
“…Universities have made explicit connections to the processes of globalization and internationalization (Engel and Siczek, 2018;EUA, 2013). Both Hammond and Keating (2018) and Friedman (2018) suggest that governments and universities, including those within the UK, are under increasing pressure to internationalize both their practice and their student cohort, while developing their global reach within a global framework of neo-liberal economic policies and practices. This engagement with global citizenship has received increasing scrutiny, leading to accusations that HEIs are overly concerned with the development of employability within the global marketplace, rather than with fostering global citizens with a deep understanding of the injustices of globalization and the competencies to affect positive societal change (Hammond and Keating, 2018).…”
Section: Teacher Education For Global Citizenship: a Literature Reviewmentioning
confidence: 99%
“…MEXT., 2013) to reconstruct Japanese education based on the principles of the revised Basic Education Law, highlighting the development of social competences where a balance between independence and collaboration is found within a society in a continuous process of transformation. Hammond and Keating (2018), through their research, have shown that in the programs of Japanese universities internationalization strategies have been promoted to maximize global competitiveness. In this way, an adaptation of education for global citizenship is carried out to fit institutional commitments.…”
Section: Academic Internationalization In the Hispanic-japanese Contextmentioning
confidence: 99%